2023
DOI: 10.1007/s40544-022-0708-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic tribological effect between polyisobutylene succinimide-modified molybdenum oxide nanoparticle and zinc dialkyldithiophosphate for reducing friction and wear of diamond-like carbon coating under boundary lubrication

Abstract: Organic molybdenum lubricant additive like molybdenum dialkyl dithiocarbamate (MoDTC) can cause wear acceleration of diamond-like carbon (DLC) coating coupled with steel under boundary lubrication, which hinders its industrial application. Therefore, polyisobutylene succinimide (PIBS), an organo molybdenum amide, was adopted to modify molybdenum oxide affording molybdenum polyisobutylene succinimide-molybdenum oxide nanoparticles (MPIBS-MONPs) with potential to prevent the wear acceleration of DLC coating. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Dynamic light scattering (DLS) and UV spectral studies showed that minimal aggregation of the carbon nanoparticles in n -decane is observed at a PIB-SI concentration of 5 wt%, which correlates with the optimized formulations for Group III and IV engine oils. An amphiphilic nature of PIB-SI was used in surface-capping of MoO 3 ; the nanoparticles modified with zinc dialkyldithiophosphate [ 150 ] demonstrated a synergistic tribological effect, reduced friction and caused wear in the diamond-like carbon coating under boundary lubrication.…”
Section: Further Transformations Of Hrpib (Pib-cl) and Applications O...mentioning
confidence: 99%
“…Dynamic light scattering (DLS) and UV spectral studies showed that minimal aggregation of the carbon nanoparticles in n -decane is observed at a PIB-SI concentration of 5 wt%, which correlates with the optimized formulations for Group III and IV engine oils. An amphiphilic nature of PIB-SI was used in surface-capping of MoO 3 ; the nanoparticles modified with zinc dialkyldithiophosphate [ 150 ] demonstrated a synergistic tribological effect, reduced friction and caused wear in the diamond-like carbon coating under boundary lubrication.…”
Section: Further Transformations Of Hrpib (Pib-cl) and Applications O...mentioning
confidence: 99%
“…They experienced reduced friction and wear on a diamond-like carbon coating during their study. During their surface analysis, they revealed some of the tribochemical reactions in the boundary layer, thereby demonstrating the fundamental operation of ZDDP and the transformation of MoO3 [35].…”
Section: Introductionmentioning
confidence: 98%
“…Despite this, nanoparticles with high thermal stability can reduce the coefficient of friction [28]. As Chen [35] did, to understand the entire operation, it is necessary to look in detail at the reactions in the boundary layer.…”
mentioning
confidence: 99%
“…The metal/metal oxide nanoparticles, a kind of typical extreme-pressure antiwear additives, tend to form the chemical reaction film under high load resistance. , Despite their excellent properties, the dispersion stability of nanoparticles in lubricating oils remains a thorny issue, which directly affects the performance and lifespan of the lubricant. Chemically modified metal/metal oxide nanoparticles used as lubricating oil additives often show defects such as complicated processes, short life, and even environmental pollution. ,, Another typical extreme-pressure antiwear agent is an organic additive containing N, S, P, Cl, and other elements, such as zinc dialkyldithiophosphate (ZDDP); , however, ZDDP also has some disadvantages that cannot be ignored, such as bad smell and an unfriendly environment . Therefore, it is extremely important to prepare a highly dispersed, environmentally friendly, and nontoxic antiwear agent.…”
Section: Introductionmentioning
confidence: 99%